MENINGKATKAN PEMAHAMAN KOSAKATA BAHASA INGGRIS MELALUI METODE PERMAINAN BINGO - Hana Nurwahidah Sudrajat; Herlina Herlina (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
The objective of this research is to investigate whether the implementation of Bingo game can increase students’ mastery of English vocabulary at the 2nd grade students of Primary School of PGSD Laboratorium in Setiabudi South Jakarta. Using the model of Kemmis and McTaggart, this classroom action research was conducted in two cycles. The subject of this research were 20 students of the 2nd grade and the data were collected using test instrument to measure students’ level of vocabulary mastery. The observation sheet was also used to record the activities of the teacher and the students when they were playing bingo game. The result of this research shows a significant increase in vocabulary mastery score after the application of Bingo game.